2014
DOI: 10.1097/01.tp.0000437435.19980.8f
|View full text |Cite
|
Sign up to set email alerts
|

Red Blood Cell Transfusions and the Risk of Allosensitization in Patients Awaiting Primary Kidney Transplantation

Abstract: Sensitization from transfusion can occur in up to 20% of transplant candidates, resulting in higher antibody levels and CPRA values that adversely impact access to transplantation. These results support transfusion avoidance whenever possible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
54
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 70 publications
(55 citation statements)
references
References 35 publications
0
54
0
1
Order By: Relevance
“…This has important implications. Recent evidence has shown that RBC transfusion can cause allosensitization [23,24] , such that the increased use of transfusions could possibly result in increased sensitization in the dialysis population overall [23,25,26] . This is important because sensitized kidney transplant candidates wait longer and their graft survival is shorter should they undergo transplant [27] .…”
Section: Discussionmentioning
confidence: 99%
“…This has important implications. Recent evidence has shown that RBC transfusion can cause allosensitization [23,24] , such that the increased use of transfusions could possibly result in increased sensitization in the dialysis population overall [23,25,26] . This is important because sensitized kidney transplant candidates wait longer and their graft survival is shorter should they undergo transplant [27] .…”
Section: Discussionmentioning
confidence: 99%
“…8, 28 In spite of the consistent finding of an association between mechanical circulatory support and allosensitization, the mechanism of sensitization has not been completely delineated. Transfusion of blood products has previously been associated with allosensitization, 29, 30 but avoidance of transfusing leukofiltered cellular blood products has not been shown to prevent it. 31 Differences in the immunogenicity of the various devices may play a role with more contemporary devices potentially posing a lower risk for allosensitization than earlier iterations of VADs.…”
Section: Discussionmentioning
confidence: 99%
“…Our study is also novel in its evaluation of the potential adverse consequences of withholding intravenous iron during active infection, particularly the possibility of increasing the rate of RBC transfusion, which may also pose risk for infection (20,21) and can lead to sensitization among patients awaiting kidney transplants (22), or higher use of ESAs. We found that transfusion was a rare event during hospitalization for infection, and we did not observe a higher risk of transfusion among patients who did not receive intravenous iron during hospital admission.…”
Section: Discussionmentioning
confidence: 99%